The aging experience diversity and commonality across cultures - Keith, Jennie (Thousand Oaks, Calif. ; London : SAGE, 1994)
In an attempt to understand the meaning of ageing and the treatment of the aged in different cultures, seven anthropologists have made studies of 10 communities on four continents - the results of which are presented in this book. The authors use both qualitative and statistical data to examine such issues as: health and well-being, perceptions of the life course, material resources, and functionality of elders.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Older people -- Cross-cultural studies; Old age -- Cross-cultural studies; Older people. -- Cross-cultural studies; Old age. -- Cross-cultural studies